A Comparative Analysis of the Biological Parts of the National Curricula in Lower Secondary Education in the Czech Republic and Selected Post-Communist Countries - Poupová, Jana; Janštová, Vanda; Kuba, Radim; Mourek, Jan (Scientia in educatione, 2019)
In the Czech Republic, a revision of the national curricular documents for primary and secondary education is being prepared and intensively discussed. The aim of this paper is therefore to contribute to the ongoing professional discussion and to select the key aspects of foreign curricular documents that may be inspiring for the Czech curricular reform. In our study, we compare the concept of the biological part of the valid national curricular documents for lower secondary education (from the 6th to the 9th grades), the second stage of basic school in the Czech Republic, with five selected post-communist European countries, namely Estonia, Hungary, Poland, Slovakia and Slovenia. We focused on the following key aspects: a) the major characteristics of biology as a school subject (or the biological part of the subject “science”); b) specification and arrangement of subject matter; c) biology as a scientific discipline; d) didactic recommendations and requirements; e) the way of treating crucial biological disciplines; f) other criteria, such as emphasis on local regions or public engagement. We consider the Estonian and Slovenian educational programmes to be the most inspiring ones, since they elaborate general educational objectives to the level of particular learning content and standards of knowledge. We also find the links to practical work and ICT and connections between biology and general competences very useful when using the documents in classroom practice. The Slovenian document offers an inspiring holistic approach to teaching of biological issues. The Estonian curriculum is a good example of incorporating local aspects, such as typical local ecosystems. The national curricula of both countries recognise biological knowledge and scientific literacy as being very important for the lives of the individual as well as for society.